2020
DOI: 10.1128/jvi.01120-19
|View full text |Cite
|
Sign up to set email alerts
|

Boosting with AIDSVAX B/E Enhances Env Constant Region 1 and 2 Antibody-Dependent Cellular Cytotoxicity Breadth and Potency

Abstract: Induction of protective antibodies is a critical goal of HIV-1 vaccine development. One strategy is to induce nonneutralizing antibodies (NNAbs) that kill virus-infected cells, as these antibody specificities have been implicated in slowing HIV-1 disease progression and in protection. HIV-1 Env constant region 1 and 2 (C1C2) monoclonal antibodies (MAbs) frequently mediate potent antibody-dependent cellular cytotoxicity (ADCC), making them an important vaccine target. Here, we explore the effect of delayed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 57 publications
3
27
1
Order By: Relevance
“…Since the specificities of the RV144 antibodies were not characterized structurally, we performed a systematic analysis of their fine epitope specificities and compared them to those induced in natural infection. We also compared them to the anti-cluster A RV305 antibody DH677.3 (28). We were able to determine the crystal antigen complex structures of two RV144 antibodies, CH54 and CH55, and map the epitopes of five additional RV144 antibodies by FRET-FCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the specificities of the RV144 antibodies were not characterized structurally, we performed a systematic analysis of their fine epitope specificities and compared them to those induced in natural infection. We also compared them to the anti-cluster A RV305 antibody DH677.3 (28). We were able to determine the crystal antigen complex structures of two RV144 antibodies, CH54 and CH55, and map the epitopes of five additional RV144 antibodies by FRET-FCS.…”
Section: Discussionmentioning
confidence: 99%
“…NCT01435135), in which a subset of RV144 vaccinees were immunized again with the same RV144 vaccine components, indicated that A32-like ADCC responses induced by ALVAC/ AIDSVAX B/E vaccine could be effectively boosted. Sera from RV305 subjects were capable of effective ADCC, and several isolated A32-like mAbs showed increased potency and breadth compared to those of A32 and mAbs isolated from RV144 subjects (28).…”
mentioning
confidence: 97%
“…Infection of primary cells. The generation of infected cells was described previously (79). Here, 3 × 10 6 cells were infected with the appropriate dose of IMC or latent reservoir virus supernatant.…”
Section: Discussionmentioning
confidence: 99%
“…Scores obtained from PC1 account for 70% variability in the affinity of the antibodies toward the LRVs. This method of calculation of ADCC score was described by Easterhoff et al (79).…”
Section: Methodsmentioning
confidence: 99%
“…Despite lower V2 response in HVTN 100 compared to HVTN 097, HVTN 100 elicited potent and cross-subtype binding antibody responses against HIV-1 envelope, with higher magnitude for multiple major epitopes compared to HVTN 097. Subsequent evaluation of the functions of the antibodies, including antibody Fc effector functions such as conformational C1-C2 antibody specificities that mediate ADCC 44 , elicited in these studies is needed to fully understand the differences in immunogenicity across these regimens. In addition, one of the objectives of testing RV144-like poxvirus-prime/ protein-boost vaccines in South Africa is to see whether the correlates of decreased HIV-1 risk identified in RV144 can be repeated by subtype C vaccines.…”
Section: Discussionmentioning
confidence: 99%